Trehalose diester glycolipids are superior to the monoesters in binding to Mincle, activation of macrophages in vitro and adjuvant activity in vivo. Issue 6 (August 2016) - Huber, Alexandra; Kallerup, Rie S; Korsholm, Karen S; Franzyk, Henrik; Lepenies, Bernd; Christensen, Dennis; Foged, Camilla; Lang, Roland
The T-cell adjuvanticity of mycobacterial cord factor trehalose 6, 6'-dimycolate (TDM) is well established. The identification of the C-type lectin Mincle on innate immune cells as the receptor for TDM and its synthetic analogue trehalose 6, 6'-dibehenate (TDB) has raised interest in development of synthetic Mincle ligands as novel adjuvants. Trehalose mono- (TMXs) and diesters (TDXs) with symmetrically shortened acyl chains [denoted by X: arachidate (A), stearate (S), palmitate (P), and myristate (M)] were tested. Upon stimulation of murine macrophages, G-CSF secretion and NO production were strongly augmented by all TDXs tested, in a wide concentration range. In contrast, the TMXs triggered macrophage activation only at high concentrations. Macrophage activation by all TDXs required Mincle, but was independent of MyD88. The superior capacity of TDXs for activating macrophages was paralleled by direct binding of TDXs, but not of TMXs, to a Mincle-Fc fusion protein. Insertion of a short polyethylene glycol between the sugar and acyl chain in TDS reduced Mincle-binding and macrophage activation. Immunization of mice with cationic liposomes containing the analogues demonstrated the superior adjuvant activity of trehalose diesters. Overall, immune activation in vitro and in vivo by trehalose esters of simple fatty acids requires two acyl chains of length and involves Mincle.